1985
DOI: 10.1002/art.1780280307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term procainamide therapy on immunoglobulin synthesis

Abstract: Procainamide is a potent inducer of autoantibodies. In order to evaluate the immunologic effects of this drug in vivo, 23 cardiac disease patients who had received procainamide for at least 6 months and an equal number of matched cardiac disease control subjects were studied, and percentage of circulating T cell subsets, concanavalin A-induced suppressor cell activity, and pokeweed mitogen-stimulated generation of immunoglobulin-secreting cells was quantitated. There was no significant difference between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…130 4. 136,137 They found that patients on long-term procainamide therapy had normal numbers and ratios of helper and suppressor T cells and normal mitogeninduced suppressor cell activity. [131][132][133][134][135][136] The reported effects on cellular immune function conflict with one another, and the described effects were small, requiring relatively high concentrations of procainamide.…”
Section: Effects On the Cellular Immune Systemmentioning
confidence: 99%
“…130 4. 136,137 They found that patients on long-term procainamide therapy had normal numbers and ratios of helper and suppressor T cells and normal mitogeninduced suppressor cell activity. [131][132][133][134][135][136] The reported effects on cellular immune function conflict with one another, and the described effects were small, requiring relatively high concentrations of procainamide.…”
Section: Effects On the Cellular Immune Systemmentioning
confidence: 99%
“…Shamess et al also found normal suppressor T-cell activity in patients taking procainamide who had ANA (52). Yu and Ziff found that cells from patients treated with procainamide had a normal ratio of helper to suppressor cells but diminished B-cell response, even in the presence of T-cells from normal subjects (53). Drug was not present during these incubations; therefore, the observations represent an irreversible effect of the drug or its metabolites on the cells.…”
Section: Possible Mechanisms Of Drug-induced Lupusmentioning
confidence: 93%
“…Con A-induced suppressor cell activity Non-specific suppressor cell activity was evaluated from 6 AS patients by a two-stage method as described by Yu et al (13). Briefly, 5x106/ml mononuclear cells were stimulated with 30 pg/ml of concanavalin A (ConA, Pharmacia Fine Chemicals, Uppsala, Sweden) and cultured at 37"C, 5 % C02 in Petri dishes, with continuous shaking for 48 h. As a control, ConA was added to the non-activated control cells just before harvest.…”
Section: Defective T Cell Function In As 45mentioning
confidence: 99%